STRUCTURE OF MESOFAUNA BY THE DIFFERENT TYPES OF FARMING - Дмитренко, І. С. (Scientific Progress & Innovations, 2014)
Set the role of soil mesofauna as the basis of all the processes of soil formation. Mesofauna composition investigated in the fields of different types of farming and calculated the relative number of invertebrates in terms of area. Results of experimental studies are presented in tabular form by June 2013. Technique has been described for studying soil fauna that has been used during the experiments. The results of two fields with different types of farming have been listed and mapped.